Updating and reasoning: Different processes, different models, different functions. (2019) - Kelly, Laura; Prabhakar, Janani; Khemlani, Sangeet
Abstract: Two issues should be addressed to refine and extend the distinction between temporal updating and reasoning advocated by Hoerl & McCormack. First, do the mental representations constructed during updating differ from those used for reasoning? Second, are updating and reasoning the only two processes relevant to temporal thinking? If not, is a dual-systems framework sensible? We address both issues below.